The performance of different types of flower-like zinc oxide for photocatalytic desulfurization of synthetic thiophene - Hamdan, Mohamad Alif Hakimi (2022)
Zinc oxide (ZnO) nanoparticles have received great attention due to their advantages. Several improvements on the morphology of ZnO have been widely studied to solve the problem of agglomeration and surface-active sites. To date, there are limited studies involving the effect of flower-like ZnO in the application of thiophene desulfurization via photocatalysis process. Thus, this study focuses on the performance of different flower-like ZnO for synthetic thiophene desulfurization. Eight ZnO photocatalyst species were synthesised and categorized into two groups, namely flower-like ZnO and non-flower-like ZnO. The physical properties of all the ZnO morphologies were analysed. Moreover, their performances for desulfurization of synthetic thiophene were evaluated. From the findings, flower-like ZnO flakes showed the highest performance in synthetic thiophene desulfurization (30%). Higher pH (pH 11) and turbidity reduction (32%) of the permeate indicated the higher generation of hydroxyl radicals causing higher desulfurization of thiophene. From the kinetic study, all ZnO morphologies were applicable with pseudo-second-order models due to higher linear regression (R2 ) values. The highest concentration equilibrium, Ce value for flower-like ZnO flakes (909.09 mg/g) confirmed greater desulfurization of thiophene. Moreover, it was found that pH 7 in the presence of 0.05 g/L flower-like ZnO flakes for 90 minutes of irradiation were the best conditions and yield the highest desulfurization of 300 ppm synthetic thiophene (30%) due to the highest generation of hydroxyl radical. It is expected that this integrated approach could bring forward other initiative methods in overcoming the problems in petroleum industry related to desulfurization of sulphur-containing compounds.